Demographic factors and marital status: Do they really influence the quality of nursing work life? - Kurniasih, Yuni; Melinda, Dina; Ramdhani, Wawan Febri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Quality of Nursing Work Life (QNWL) is a crucial factor influencing nurses' well-being and performance. Although demographic factors, including marital status, are often considered determinants of QNWL, research findings on their impact remain inconsistent. Purpose: To assess whether demographic factors and marital status, have a significant impact on the Quality of Nursing Work Life (QNWL) among nurses. Method: A cross-sectional design involving 72 nurses working in inpatient care units. Data were collected using a validated QNWL questionnaire and analyzed using Spearman’s rank correlation test to evaluate the relationship between marital status and QNWL. Results: The majority of nurses reported their QNWL as